2015
DOI: 10.1158/1535-7163.mct-15-0121
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Involved in EGFR Turnover Are Predictive for Cetuximab Efficacy in Colorectal Cancer

Abstract: Transmembrane receptors such as the epidermal growth factor receptor (EGFR) are regulated by their turnover, which is dependent on the ubiquitin-proteasome-system (UPS). We tested in two independent study cohorts whether single nucleotide polymorphisms (SNPs) in genes involved in EGFR turnover predict clinical outcome in cetuximab treated metastatic colorectal cancer patients. The following SNPs involved in EGFR degradation were analyzed in a screening cohort of 108 patients treated with cetuximab in the chemo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…EGFR activation is responsible for the cellular secretion of proteins involved in antimicrobial defense (Pastore et al, 2008). A number of single-nucleotide polymorphisms identified as predictive for anti-EGFR therapy are involved in the trafficking and internalization of EGFR, including polymorphisms in c-CBL and EPS15 (Stintzing et al, 2015), suggesting that polarization or dysregulation of EGFR trafficking may in part determine patient therapeutic response.…”
Section: Ak Iec and Scc Lesions Show Differential Endocytosis Pattementioning
confidence: 99%
“…EGFR activation is responsible for the cellular secretion of proteins involved in antimicrobial defense (Pastore et al, 2008). A number of single-nucleotide polymorphisms identified as predictive for anti-EGFR therapy are involved in the trafficking and internalization of EGFR, including polymorphisms in c-CBL and EPS15 (Stintzing et al, 2015), suggesting that polarization or dysregulation of EGFR trafficking may in part determine patient therapeutic response.…”
Section: Ak Iec and Scc Lesions Show Differential Endocytosis Pattementioning
confidence: 99%
“…(82) EGFR recycling could be an interesting mechanism of secondary resistance to cetuximab in mCRC and is also a putative mechanism for PTEN induced EGFRi resistance. (28,82) Further studies are needed to validate these preliminary data.…”
Section: Map-kinase Pathway Alterations As Mechanisms Of Acquired Resmentioning
confidence: 98%
“…Single nucleotide polymorphisms (SNPs) in candidate genes associated with regulating the EGFR pathway communication also appeared to be of predictive value in several reports. (82) In particular, Stintzing et al have identified SNPs in genes involved in EGFR turnover that predicted clinical outcome in cetuximab-treated mCRC patients. (82) EGFR recycling could be an interesting mechanism of secondary resistance to cetuximab in mCRC and is also a putative mechanism for PTEN induced EGFRi resistance.…”
Section: Map-kinase Pathway Alterations As Mechanisms Of Acquired Resmentioning
confidence: 99%
“…The therapeutic efficacy of cetuximab is often compromised by acquired drug resistance; however, the mechanisms underlying this phenomenon are still unknown. Computer simulations have shown that multiple ubiquitination-related protein gene polymorphisms are involved in EGFR turnover and predict the efficacy of cetuximab, such as the ubiquitin-binding enzyme UBE2M and ubiquitin-conjugating enzyme E2L3 (UBE2L3), which may affect secondary resistance to cetuximab in metastatic CRC (Stintzing et al 2015 ). Moreover, previous reports have shown that resistance to cetuximab in CRC is associated with increased expression of c-Myc, which significantly reduces apoptosis (Boos et al 2022 ).…”
Section: Chemotherapy Drugsmentioning
confidence: 99%